Analisis Proksimat pada Beras Ketan Varietas Putih (Oryza sativa glutinosa) - Suriani Suriani (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2015)
It has done research on Proximate Analysis On White Glutinous Rice Varieties (Oryza sativa glutinosa) Origin Sinjai Regency with the aim to determine the content prosimat include moisture content, ash content, crude proteincontent, fat content, crude fiber content and total carbohydrate content contained on white glutinous rice varieties (Oryza sativa glutinosa) origin Sinjai regency. This type of research is experimental research is a research laboratory that uses a simple experiment. At the proximate analysis includes determination of moisture content (%), protein content (%), fat content, ash content (%), crude fiber levels, total carbohydrate(%). The results showed that the water content ranges for % 16.24%, for protein content ranged from 6.81%, forfat content ranged from 0.19 % to 0.24% ash content ranges, for fiber content ranged from 0.28% and for carbohydrate content ranged from 76.24 %.